1997
DOI: 10.1073/pnas.94.16.8557
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore structural changes in rhodopsin from nanoseconds to microseconds following pigment photolysis

Abstract: Rhodopsin is a prototypical G proteincoupled receptor that is activated by photoisomerization of its 11-cis-retinal chromophore. Mutant forms of rhodopsin were prepared in which the carboxylic acid counterion was moved relative to the positively charged chromophore Schiff base. Nanosecond time-resolved laser photolysis measurements of wild-type recombinant rhodopsin and two mutant pigments then were used to determine reaction schemes and spectra of their early photolysis intermediates. These results, together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 53 publications
3
35
0
Order By: Relevance
“…The nuclear spin interactions in solid-state 2 H NMR 24 as well as the electronic transition dipole moment 46 transform by the totally symmetric representation of the D ∞h point group. They are invariant to the symmetry operations of inversion, rotation, or reflection as found in standard character tables.…”
Section: Modeling Retinal Conformation In Dark Statementioning
confidence: 99%
See 2 more Smart Citations
“…The nuclear spin interactions in solid-state 2 H NMR 24 as well as the electronic transition dipole moment 46 transform by the totally symmetric representation of the D ∞h point group. They are invariant to the symmetry operations of inversion, rotation, or reflection as found in standard character tables.…”
Section: Modeling Retinal Conformation In Dark Statementioning
confidence: 99%
“…Analogous electronic transition dipole (TD) orientations are denoted by and θ TD . The Ci-Ck bond angle to the local membrane normal is , and is calculated from the C9 methyl the orientation, together with the transition dipole in either the dark 44,46 or meta I 43 state. According to Eq.…”
Section: Calculation Of Effective Torsional Anglesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, NMR studies by Watts and co-workers, 41 as well as theoretical work by Birge and coworkers, 42 concluded that the chromophore geometry is 6s-trans at the C6-C7 bond, in contrast to the 6s-cis conformation assumed by earlier NMR and optical studies. 33,43,[45][46][47][48][49][50] To address the orientation of the -ionone ring, according to rigorous DFT QM/MM calculations, a computational model of the 6s-trans isomer has been constructed by geometry relaxation of the system after rotation of the -ionone ring around the C6-C7 bond. 2 The resulting 6s-trans structure, obtained at the ONIOM electronicembedding (B3LYP/6-31G*:Amber) level of theory, was found to be as stable as the 6s-cis isomer for many thermally accessible configurations and about 8 kcal/mol less stable than the 6s-cis structure when minimum energy geometries are compared.…”
Section: Orientation Of the -Ionone Ringmentioning
confidence: 99%
“…Remarkably, upon absorbing a photon it instantly isomerizes (within 200 fs 17,22 ) to the all-trans state, and subsequently becomes an agonist 13,14 . The protein relaxes through a series of spectroscopically defined intermediates 23 until it reaches the MI state, which exists in equilibrium with the active MII state 13,14,16,18 . The central role of retinal in directing this relaxation and promoting MII formation has been extensively investigated by a number of approaches.…”
Section: Introductionmentioning
confidence: 99%